Simpatria entre duas espécies de peixes invertívoras de Bertioga (SP) - Silva, Victoria Pinheiro Gonçalves da (2018)
The objective of this work was to verify the feeding overlap between two caracids fishes, Hollandichthys multifasciatus and Mimagoniates microlepis, in 11 coastal streams in Bertioga (SP), as well as to describe the diet of both species and verify the occurrence of seasonal and spatial variation over a year. The sampling sites are located in the municipality of Bertioga (SP). The samplings were monthly done from may/2016 to april/2017 with the aid of electric fishing. The specimens collected were anesthetized and dissected, in which the stomachs were removed and stored in ependorf for future analysis. The food items were divided into 17 categories according to their origin: allochthonous, autochthonous and unknown. The frequency of occurrence and volume of each item ingested was combined to form the food index. Bray-Curtis similarity, followed by clustering, was used to identify spatial-temporal variations in fish diet. A redundancy analysis was used to verify the influence of environmental data on the items consumed. The Morisita index was calculated to identify the degree of food overlap between the two species. Both species demonstrated an invertivore feeding habit with tendency to terrestrial invertivory. The sazonal variation observed for H. multifasciatus and M. microlepis occurred in the volume of adult terrestrial insects ingested. Also, a diet shift was observed among streams, the fishes category became the most consumed by H. multifasciatus in streams 5 and Decapoda in streams 7 and 11, and M. microlepis fed large quantities of immature aquatics insects in strems 5 and 9. The RDA showed that environmental variables that best explained the axes and influencied the most in the diet composition were gravel and litter. The food overlap, in gerenal, was moderate between periods, streams and stretches, except strems 3, 4 and 10 which presented high overlap.